Green hotel ; customers awareness of environmental responsibility (ER) and their intention to purchase / Irina Mohd Akhir - Mohd Akhir, Irina (2013)
In this study it is examined on the Environmental Awareness in hospitality industry, looking into the level of awareness, the factors of awareness and the relationship towards the purchase intention. For this study context, it is concern towards the intention to patronize Green Hotels focusing on matters such as the argument whether Environmental Responsibilities (ER) conscious in oneself will influence the behavior of hotel guest. This study applying the sample test on context of potential customers of Green Hotels in Penang Island. This study focusing onto three objectives, (1) identifying the influencing factors of ER awareness towards purchase intention, (2) Identifying the relationship of ER awareness and purchase intention, and (3) Which is the most influencing factors (ER marketing, ER knowledge, ER social influence) of ER awareness towards purchase intention. A statistical analysis was conducted using a descriptive study which employed a quantitative study and correlation study. The data gathering process will involves collections of secondary data to convey literature studies. Convenience sampling and self administered questionnaire was used. A pilot test was conducted and in effort to redefine the betterment of the questionnaire While related data processing inclusive the use of descriptive statistic, Pearson correlation, multiple regression analysis, factor analysis and reliability analysis. The theoretical relationships of this study were empirically supported, and the regressed analysis has come up with the most influencing factors in Malaysian context.